TRADISI TAHLILAN DAN YASINAN - Rhoni Rodin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
This paper discusses about the values which contain in tahlian andyasinan in Muslim societies as aseries activities in takziyah. Takziyah isvisiting the family which one of the member is died.this research is intendedto know the detail activity of tahlian and yasinan which becomethe source to dig up the values inside. Both tahlian and yasinan containsspecial values which support the live of the society and it mixes with thelocal culture.